Meningkatkan aktivitas dan hasil belajar kimia siswa melalui penerapan model learning cycle - Ahmadurifai Ahmadurifai (Indonesian Journal of Educational Development, 2020)
This research is a classroom action research conducted in two cycles. The action applied in this research is the Learning Cycle Model in chemistry learning. The subjects of this study were students of SMA Negeri 1 Hu'u class XI IPA 4 odd semesters of the 2019/2020 school year. The object of this research is student learning activities, student learning outcomes and student opinions due to the application of the Learning Cycle model. Student learning activity data were collected using observation sheets, chemistry learning outcomes were collected using learning outcomes tests, and student response data were collected using a questionnaire. The results showed that the Learning Cycle model which is applied in learning chemistry, can improve: 1) student learning activities and 2) student learning outcomes, and 3) students give a positive response to the applied learning model. The increase in student learning outcomes can be seen from the increase in the mean value, where in the first cycle it was 60.31 to 66.03 in the second cycle. The success of implementing the learning model can also be seen from the increase in student learning completeness, from 53.85% in cycle I to 73.08% in cycle II. Students gave a positive response to the application of the learning model, where there were 70.41% of students who agreed, 20.71% had doubts, and only 8.88% did not agree with the application of the Learning Cycle model.   Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam dua siklus. Tindakan yang diterapkan pada penelitian ini adalah Model Learning Cycle dalam pembelajaran kimia. Subjek dari penelitian ini adalah siswa SMA Negeri 1 Hu’u kelas XI IPA 4 semester ganjil tahun pelajaran 2019/2020. Objek penelitian ini adalah aktivitas belajar siswa, hasil belajar siswa dan pendapat siswa akibat penerapan model Learning Cycle. Data aktivitas belajar siswa dikumpulkan menggunakan lembar observasi, hasil belajar kimia dikumpulkan menggunakan tes hasil belajar, dan data respon siswa dikumpulkan menggunakan kuesioner. Hasil penelitian menunjukkan bahwa model Learning Cycle yang diterapkan dalam pembelajaran kimia, dapat meningkatkan: 1) aktivitas belajar siswa dan 2) hasil belajar siswa, serta 3) siswa memberikan respon positif terhadap model pembelajaran yang diterapkan. Peningkatan hasil belajar siswa dapat dilihat dari peningkatan rerata nilai, di mana pada siklus I sebesar 60,31 menjadi 66,03 pada siklus II. Keberhasilan penerapan model pembelajaran juga dapat dilihat dari peningkatan ketuntasan belajar siswa, dari 53,85% pada siklus I menjadi 73,08% pada siklus II. Siswa memberikan respon positif terhadap penerapan model pembelajaran, di mana terdapat 70,41% siswa yang menyatakan setuju, 20,71% ragu-ragu, dan hanya 8,88% tidak setuju dengan penerapan model Learning Cycle.